Characterization of igaB, a Second Immunoglobulin A1 Protease Gene in Nontypeable Haemophilus influenzae - Fernaays, Matthew M. (American Society for Microbiology, 2006)
Nontypeable Haemophilus influenzae is an important respiratory pathogen, causing otitis media in children and lower respiratory tract infection in adults with chronic obstructive pulmonary disease (COPD). Immunoglobulin A1 (IgA1) protease is a well-described protein and potential virulence factor in this organism as well as other respiratory pathogens. IgA1 proteases cleave human IgA1, are involved in invasion, and display immunomodulatory effects. We have identified a second IgA1 protease gene, igaB, in H. influenzae that is present in addition to the previously described IgA1 protease gene, iga. Reverse transcriptase PCR and IgA1 protease assays indicated that the gene is transcribed, expressed, and enzymatically active in H. influenzae. The product of this gene is a type 2 IgA1 protease with homology to the iga gene of Neisseria species. Mutants that were deficient in iga, igaB, and both genes were constructed in H. influenzae strain 11P6H, a strain isolated from a patient with COPD who was experiencing an exacerbation. Analysis of these mutants indicated that igaB is the primary mediator of IgA1 protease activity in this strain. IgA1 protease activity assays on 20 clinical isolates indicated that the igaB gene is associated with increased levels of IgA1 protease activity. Approximately one-third of 297 strains of H. influenzae of diverse clinical and geographic origin contained igaB. Significant differences in the prevalence of igaB were observed among isolates from different sites of isolation (sputum > middle ear > nasopharynx). These data support the hypothesis that the newly discovered igaB gene is a potential virulence factor in nontypeable H. influenzae.